A extrafiscalidade nos impostos brasileiros como instrumento jurídico-econômico para a promoção de defesa do meio ambiente ecologicamente equilibrado - Birnfeld, Liane Francisca Hüning (2013)
This paper addresses tax, environmental and economic law, more precisely the use of environmental "extrafiscality" as a possible legal-economic tool to protect an ecologically balanced environment, considering the provisions in articles 225 and 170, item VI of the Federal Constitution, which set forth that everyone is entitled to an ecologically balanced environment and charge the public authorities and society at large with the duty of conserving and protecting it, including by means of different treatments according to the environmental impact of products and services and their manufacturing and supply processes. The approach method is inductive; the procedure method is monographic, and research techniques include review of the literature, legislation, jurists' works, and court decisions. The first part of the text is dedicated to examining the Social-Environmental State and the power to levy taxes, divided into two chapters that are necessary and complementary to understand the assignment of the extrafiscal role as a legal tool to foster environmental conservation. The second part of the paper investigates whether the environmental extrafiscality of taxes is constitutional, and outlines the limits of its application in the Brazilian socialenvironmental state in an effort to show that the extrafiscality may serve as a tool to implement the different economic treatment provided for in item VI, article 170 of the Constitution. Based on those premises, we finally look into the possible assignment of the environmental extrafiscal role to all existing taxes, without the need of creating new taxes. We also analyze if the taxable event is directly related to the externality produced in order to determine whether all taxes similarly lend themselves to helping protect the ecologically balanced environment or not. As the ultimate task, the thenconsolidated hypothesis of this thesis is applied to analyze the possibility of assigning the environmental extrafiscal role to the Brazilian vehicle tax and its environmental conservation potential.